2013
DOI: 10.1016/j.ijid.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing ciprofloxacin and cefepime in febrile neutropenic patients with hematological malignancies

Abstract: We could not prove the non-inferiority of CPFX in comparison with CFPM for the initial treatment of FN. CFPM remains the standard treatment of choice for FN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…This integrative review located a sample of 12 articles (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) which met the inclusion criteria and are presented in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This integrative review located a sample of 12 articles (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) which met the inclusion criteria and are presented in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the interventions for management of CT-induced FN, there was a prevalence of studies focused on pharmacological treatment (use of empiric ABT in hospital and outpatient settings, adherence to an antimicrobial management protocol and use of prophylactic or non-prophylactic growth factor) (14)(15)(18)(19)(20)(21)(22)(23)(24) and improvement in the diagnostics (association of biomarkers with the MASCC risk index) (17) . Only one study (16) investigated pharmaceutical management in relation to the efficacy of antibiotic dosage and a study which implied that nurses could contribute to the identification of elderly patients who would benefit from prophylactic use of growth factor in order to reduce the occurrence of FN (13) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…evaluated the efficacy of CFPM in patients with FN whose median age was 61 in a randomized controlled trial, and efficacy was noted in 19/25 (76.0%). 20 Regarding oral fluoroquinolone monotherapy, Chamilos et al . demonstrated that moxifloxacin was effective for 50/55 (91%) outpatients with a median age of 62 years.…”
Section: Discussionmentioning
confidence: 99%